2015
DOI: 10.1039/c5ra18927f
|View full text |Cite
|
Sign up to set email alerts
|

Integration of MnO@graphene with graphene networks towards Li-ion battery anodes

Abstract: . (2015). Integration of MnO@graphene with graphene networks towards Li-ion battery anodes. RSC Advances: an international journal to further the chemical sciences, 5 (117), 96681-96684.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…S3a †), which can be ascribed to the conversion reaction 25,29 from CoO to Co. It is interesting to note that the initial reduction peak at 0.6 V is found to shi to 0.42 V, which can be assigned to the redox conversion reaction 30 of MnO. Such a shi is also observed for the pure MnO/G aer the second and third cycles (Fig.…”
Section: Resultssupporting
confidence: 54%
“…S3a †), which can be ascribed to the conversion reaction 25,29 from CoO to Co. It is interesting to note that the initial reduction peak at 0.6 V is found to shi to 0.42 V, which can be assigned to the redox conversion reaction 30 of MnO. Such a shi is also observed for the pure MnO/G aer the second and third cycles (Fig.…”
Section: Resultssupporting
confidence: 54%
“…The ZnO/C slices were washed using 6 mol L −1 aqueous HCl solution to form porous carbon nanosheets. These carbon nanosheets were washed by deionized water and absolute ethanol, then dried in vacuum at 50°C for 8 h. Similar process was used to prepare the MnO/graphene composite using oleic acid as carbon sources (Guo et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Thus, to obtain better electrochemical properties, the contents of conduction materials should be increased. It has been found that the embedding of anode materials in carbon/graphene matrixes can realize high content of conductive carbon materials for enhanced electrochemical properties (Fu et al, 2015; Guo et al, 2015; Choi et al, 2016; Sun et al, 2016). Motivated by the above potentials, we have prepared porous NaTi 2 (PO 4 ) 3 nanocubes anchored on porous carbon nanosheets (NaTi 2 (PO 4 ) 3 /C) through ultrasonic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, a 2D sheet of sp 2 -hybridized, networked carbon, has received considerable attention due to its unique properties, such as its high surface area, and unique mechanical, thermal, and structural properties, since its discovery in 2004. 1 The use of graphene is promising in various applications, such as in supercapacitors, 2 Li-ion batteries, 3,4 sensors, 5 composite additives, 6 transparent conducting electrodes, 7 fuel cells, 8 eldeffect transistors, 9 and photovoltaic cells. 10 Graphene is produced by two types of methods: bottom-up and top-down methods.…”
Section: Introductionmentioning
confidence: 99%